Public Accounting Firm Characteristics on the Readability of Key Audit Matters - Santy, Dila Viera; Rosadi, Samsul (JAFFA, 2024)
This study investigates the readability of Key Audit Matters (KAM) in a sample of 448 companies listed on the Indonesia Stock Exchange (IDX) using the INDX model and multiple regression analysis. The findings reveal that auditors from Big Four firms, auditor gender, meeting frequency, and company leverage negatively affect KAM readability, resulting in lower INDX scores and more complex reports. Conversely, factors such as audit fees, auditor experience, KAM type, audit committee size, and company size based on total assets do not significantly influence readability. A higher INDX score indicates better readability, suggesting that reports with lower scores are more difficult to understand. These findings provide insights for regulators and auditors to improve the clarity of audit reports, enhancing transparency and communication with stakeholders.